2017
DOI: 10.1186/s12933-017-0561-3
|View full text |Cite
|
Sign up to set email alerts
|

In vivo administration of urolithin A and B prevents the occurrence of cardiac dysfunction in streptozotocin-induced diabetic rats

Abstract: BackgroundEmerging evidence suggests that specific (poly)phenols may constitute new preventative strategies to counteract cell oxidative stress and myocardial tissue inflammation, which have a key role in the patho-physiology of diabetic cardiomyopathy. In a rat model of early diabetes, we evaluated whether in vivo administration of urolithin A (UA) or urolithin B (UB), the main gut microbiota phenolic metabolites of ellagitannin-rich foods, can reduce diabetes-induced microenvironmental changes in myocardial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
93
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 114 publications
(103 citation statements)
references
References 52 publications
9
93
0
1
Order By: Relevance
“…Application of folic acid has positive effect on glucose level since it attenuates hyperglycaemia (however, glucose level values remained still higher than 11 mmol/l) in diabetic rats. DM type I is characterized by body mass loss (Gimenes et al 2015;Savi et al 2017). All our diabetic animals had decreased body mass, and the folic acid treatment did not have any influence on it.…”
Section: Discussionmentioning
confidence: 72%
“…Application of folic acid has positive effect on glucose level since it attenuates hyperglycaemia (however, glucose level values remained still higher than 11 mmol/l) in diabetic rats. DM type I is characterized by body mass loss (Gimenes et al 2015;Savi et al 2017). All our diabetic animals had decreased body mass, and the folic acid treatment did not have any influence on it.…”
Section: Discussionmentioning
confidence: 72%
“…This process leads to the production of urolithin A, urolithin B, urolithin C, and urolithin D. Urolithins have been shown to regulate cellular processes involved in normal and pathological conditions (Espín et al, ; Kang, Kim, Tomás‐Barberán, Espín, & Chung, ; Tang et al, ). A few recent studies have also reported that administration and consumption of these colonic metabolites, in particular urolithin A, promote positive health outcomes in animal models (Ryu et al, ; Savi et al, ; Tang et al, ). However and until now, the pharmacological effect of urolithins on endocrine pancreatic function has not been determined.…”
Section: Discussionmentioning
confidence: 99%
“…The multi‐target nature of urolithins as well as their effect on Ca 2+ signalling, at least for urolithin C, may possibly raise some concerns regarding their low selectivity and potential toxicity and thus constitute a drawback for their use in vivo. Nevertheless, until now, in vivo administration of urolithins failed to demonstrate any safety concerns (Heilman, Andreux, Tran, Rinsch, & Blanco‐Bose, ) but was rather found to exert a protective role and to ameliorate age‐related conditions (Ryu et al, ; Savi et al, ; Tang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…U847000) was dissolved in DMSO (50 mg/mL) and further diluted with saline immediately before intraperitoneal (ip) injections. Mice were given an intraperitoneal injection of 2.5 or 5.0 mg/kg of Uro‐A as previously described, for 24 hours and 1 hour before surgery. Mice were grouped into a sham, sham + Uro‐A, MCAO, and MCAO + Uro‐A groups.…”
Section: Methodsmentioning
confidence: 99%